The forgotten scholar : Georg Zoëga (1755-1809) : at the dawn of Egyptology and Coptic studies - Ascani, Karen.; Buzi, Paola.; Picchi, Daniela. (Culture and History of the ancient Near East ;, 2015)
"Renowned for his work within the fields of Numismatics, Archaeology, Egyptology and Coptic studies, Georg Zoëga was a figure of outstanding importance both in Rome and in Europe, at the end of the eighteenth century. Although highly valued by his contemporaries, Zoëga's scientific legacy fell almost entirely into oblivion with the end of the Enlightenment. The Forgotten Scholar : Georg Zoëga (1755-1819) : At the Dawn of Egyptology and Coptic Studies represents an exceptional occasion to rediscover the largely unknown scientific legacy of this Danish scholar consisting of hundreds of letters, drawings, sketches, notes, and other documents, mainly preserved in the Royal Library and in the Thorvaldsen Museum of Copenhagen" -- Provided by publisher.